KARAKTERISTIK SIFAT MEKANIK KOMPOSIT SANDWICH GRC-STYROFOAM - Refki Hernandes; A Sofwan F Alqap; Saeful Rohman (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2024)
The composite material made is a sandwich composite, GRC-mortar. This system is composed of a combination of laminae with others through a wiremesh that binds Styrofoam. This composite system is used as an earthquake-resistant house wall, which is expected to be not only lightweight, but also rigid and strong, the mechanical testing involved is bending testing to determine the bending strength and modulus of elasticity of the variation in mortar massa of 20 kg, 30 kg and 40 kg. the highest bending strength is 0.88 Mpa given massa mortar 20 kg, the lowest bending value is given over a mass of 30 kg, which is 0.79 MPa. The highest modulus of elasticity is 30 kg of mortar mass, which is 0.005 MPa, while the massa of 20 kg and 40 kg of mortar has a modulus of elasticity value of 0.003 MPa respectively. The composite that provides optimal strength is at a mass of 20 kg, in addition to being quite resistant to high bending strength.